GREEN HUMAN RESOURCE MANAGEMENT, CUSTOMER ENVIRONMENTAL COLLABORATION AND THE ENABLERS OF GREEN EMPLOYEE EMPOWERMENT: ENHANCHING AN ENVIRONMENTAL PERFORMANCE - Hutomo, Arry; Theresia Marditama; Nandan Limakrisna; Ilham Sentosa; John Lee Kean Yew (Dinasti Publisher, 2020)
Researchers have shown that both of green human resources management (GHRM) practices and customer environmental collaboration enhance environmental performance. However, existing literatures not be able to explain well how relationship between GHRM practices, customer environmental collaboration (CEC), the enablers of employee green empowerment and environmental performance. We conduct a medium-scale survey 125 employees at Indonesia manufacturing which have label green certificates by Green Label Indonesia (GLI-Certificates). SEM-AMOS is choosing as statistical methodology and tools that uses a confirmatory approach to data analysis. Our paper contributes to HRM and SCM theory in terms of utility and originality of research by explaining that the enablers employee green empowerment positively mediates the relationship between GHRM practices, customer environmental collaboration and environmental performance. Finally, we address potential implications of this research for developing framework to future formulations of responsible employee’s green abilities as managers.